2010
DOI: 10.12934/jkpmhn.2010.19.4.349
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dementia Education Program on Certified Geriatric Caregivers in a Nursing Home

Abstract: Purpose: This study was done to evaluate the long-term effects of a dementia education program for certified geriatric caregivers (CGCs) caring for elders with dementia in a nursing home. Methods: The research design was one group pretest-posttest design and included 29 CGCs who completed the pre-test, dementia education program, and post-test (immediately after, 1 month after, and 3 months after the completion of the program). The education program was conducted for 3 weeks, and effects of the program were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The knowledge of dementia was similar to that of the present study, although the knowledge of dementia knowledge after three dementia education programs was not statistically significant in posttraumatic care hospitals [12] [13]. Therefore, it is suggested that the development of a program to improve the knowledge of dementia at the time of education is necessary.…”
Section: Discussionsupporting
confidence: 74%
“…The knowledge of dementia was similar to that of the present study, although the knowledge of dementia knowledge after three dementia education programs was not statistically significant in posttraumatic care hospitals [12] [13]. Therefore, it is suggested that the development of a program to improve the knowledge of dementia at the time of education is necessary.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the education requirement for dementia was relatively high at 121 points out of 160, and the items with the highest demand included methods of coping with dementia patients' violent behavior, wandering, refusal to receive care, sleep disorders, delirium, delusions, etc. In other previous studies, caregivers answered that coping with problem behaviors occurring while caring for dementia patients was the most difficult in practice, and they expressed the need for practical education [11]. As such, caregivers are complaining of various difficulties in caring for dementia patients.…”
Section: Introduction 1backgroundmentioning
confidence: 95%
“…This necessitates professional and systematic training as well as caregiver training for patients with dementia [3,4]. The systematized job training of caregivers for dementia can improve their knowledge of dementia and professional functions, helping to nurture specialized caregivers for dementia [5,6]. More importantly, the cultivation of professional knowledge and a positive attitude toward caring for people with dementia are the key requirements for a caregiver for older adults with dementia [7,8].…”
Section: Introductionmentioning
confidence: 99%